Perancangan Interior Wedding House di Surabaya dengan konsep âTouch and Personal Whiteâ - Poppy F. Nilasari, Adelia Irena Martino Dwi Nugroho (Intra, 2014)
Wedding House which is located in Surabaya, is a wedding service design project. In this design, all of the facilities will be provided in one area so that the bride and groom do not need a lot of time for searching the wedding needs. These facilities are wedding organizer, invitation and souvenir area, tarts area, decoration and lighting area, documentation, bridal and salon, accessories area, and ballroom. These areas will be applied as retails and serving the special needs for the wedding. Of differences the character of each area, Wedding House will merge into a single concept that would create characters from Wedding House itself. Wedding House will be designed according the style of western wedding. Therefore, form application and interiorâs character will be design in modern style. By applying the one-stop wedding service system, Wedding House will focus on efficiency and productivity of work so that fulfill the wedding needs.